Heavy Metal Contamination of Selected Foods from the Oil Producing State of Akwa Ibom in Southern Nigeria - Abiante, Awaji-Inombek. D.; Eze, John. I.; Eze, Chinwendu. R. (Pakistan Journal of Nutrition, 2019)
Background and Objective: Heavy metals represent an important category of bio-toxic substances that are encountered under various environmental and occupational circumstances. The toxicity of these metals is in part due to their tendency to accumulate in biological tissues, a process known as bioaccumulation that can result from exposure to metals in foods of plant and animal origin. In this study, a survey was carried out to assess the awareness of residents of eight communities in the Akwa Ibom state in Nigeria about heavy metal contamination. Materials and Methods: Standard methods were used to analyse the amounts of the most dominant heavy metals in seven varieties of foods procured from selected farms in these communities as well as microbial contamination of these food samples. Questionnaires were administered for the survey studies. Data generated from the analysis were subjected to one-way analysis of variance and accepted at the 0.05 probability level. Results: All of the survey respondents were between 31 and 60 years-old and 55.1% were male. The awareness of heavy metal contamination, particularly of arsenic and lead (22.5 and 28.8%, respectively), was high. There was no fecal contamination detected in foods sampled from main urban areas. Lead, mercury and copper accumulation was most pronounced in food samples from communities located in riverine areas that are subjected to oil exploration and exploitation. There were also high amounts of heavy metal accumulation in samples from communities having a strong agriculture and commercial presence. The heavy metal content and microbial load of the various food samples varied significantly (p